Estado e território no Brasil: reflexões a partir da agricultura no Cerrado - Inocêncio, Maria Erlan; Calaça, Manoel (Universidade Federal Rural do Rio de Janeiro, 2015)
The space changes resulting from the modernization process of Cerrado were driven by productive restructuration of capital, to expand its borders toward the heartland of Brazil, promoted a (re)ordering of natural and artificial elements, interfering in the production paradigm. The dynamics of appropriation of the Cerrado were based on strategies from the state initiative, wich agricultural field was the privileged area of action. The state capital was present in the territorial politics since 1930, with the March to the West, was consolidated with Target Plan of JK (1956), in the construction of Brasilia (1960) and expanded during the Military Regime (1964), to carry out the strategy of thinking about the country from the standpoint of integration. The article is grounded in the various state actions, particularly those intended for the field, notably the Cooperation Programme Japan-Brazilian Cerrado Development, which changed the territory of the Cerrado, inserting it into a new productive dynamic in which the relations of power placed him as the focal point of the territorialization of the capital in the country. The data presented in this article are the result of literature research and field research was made during the construction of the doctoral thesis as a way of combining theory and empiricism.